Peran Inovasi Telekomunikasi Digital Mempercepat Transformasi dan Daya Saing Ekonomi Global Indonesia - Hartanto, Sri (Jurnal Multidisiplin Ibrahimy, 2026)
The rapid growth of digital devices in the telecommunications sector has become a major driver of the global economy. It is pushing Indonesia to adapt to increase national competitiveness towards the Vision of Golden Indonesia 2045. Digital communication innovations, such as 5G networks, the Internet of Things (IoT), and data-based services, play a crucial role in accelerating national economic transformation by increasing efficiency, connectivity, and productivity across sectors. Therefore, it is important to examine the extent to which telecommunications digitalization strengthens global competitiveness while reducing economic disparities between regions. This study uses a descriptive qualitative method, drawing on literature analysis, secondary data, and case studies in the digital finance sector, the manufacturing industry, and public services based on telecommunications technology. Empirical analysis shows that internet penetration in Indonesia has increased consistently during the 2022–2025 period, from around 67 percent in 2022 to 69 percent in 2023, then rising to 71 percent in 2024, and reaching around 72 percent in 2025. This trend reflects the continued growth in information technology adoption. National Gross Domestic Product (GDP) growth remained relatively stable at around 5 percent during the same period, with little variation. The study's findings indicate that telecommunications digitalization serves as a structural catalyst, accelerating economic transformation, expanding financial inclusion, improving public governance efficiency, and strengthening the competitiveness of the national industry. In conclusion, digital telecommunications innovation is a strategic foundation for Indonesia's more efficient, inclusive, globally competitive, and sustainable economic development.